Effect of temperature on the expression of IFN-1 (α), STAT-1 and Mx-1 genes in Oncorhynchus mykiss (Salmoniformes: Salmonidae) exposed with the virus of the infectious pancreatic necrosis (IPNV) - Arguedas Cortés, Donald (2015)
The infectious pancreatic necrosis (IPNV) is the causative agent of an acute illness well characterized in salmonids worldwide. Clinical signs and mortality rates are dependent on several factors such as the viral dose, the age of the fish, the water temperature, among others. An experimental study was conducted to measure the effect of temperature on the gene expression profile of IFN-1(α), STAT-1 and Mx-1 in rainbow trout fry, exposed to IPNV. Fry (n=198) were exposed at 8, 12 and 16°C, and samples were taken for 21 days to determine the virus titer and gene expression. In the first 11 days the greatest viral titer was recorded at 8°C compared with the values obtained at 12 and 16°C.  At 8°C, there was a significant increase on day 4 of mRNA Mx-1 (t-test, p<0.05), time in which the viral titer began to decrease. Furthermore, as the viral titer increased, STAT-1 and Mx-1 (r=0.91) and (r=0.96) increased, respectively. The animals were able to recover from day 4 from some of the symptoms of IPN. Clinical disease was developed only in fish exposed to 12°C and all died between days 6 and 14, despite the highly significant increase shown in the average expression level of Mx-1, compared with the values recorded at 8°C and 16°C (Tukey, p<0.0001). Additionally, the expression profiles of IFN-1(α) and STAT-1 decreased completely (~0.016) and (~0.020 times) on day 7. The highest expression level of IFN-1(α), occurred at 16°C (Tukey, p<0.0005). Fry exposed at 16°C were normal during the experiment. IFN-1(α) possibly generated a protector effect from day 2 when they showed a significant expression increase compared with the results at 8°C and 12°C (t-student, p<0.0001); however, STAT-1 was not significantly affected by temperature, although the highest average expression value was recorded at 16°C. Our research supports the expression of relevant anti-viral response genes as IFN-1(α), STAT-1 and Mx-1 are physiologically modulated by the water temperature, directly influencing the development of the IPN disease in rainbow trout.